(untitled) (American Journal of Islam and Society, 1991)
The author, Issa Boullata, states that his intention is to study Arab intellectual and social phenomena and trends against the background of modernity: “Particularly insufficient in Western studies are publications on Arab intellectuals who are grappling with the idea of modernity” (p. ix). Furthermore, “this book, concerned with the present-day Arab culture and its crisis, will attempt to present a number of important themes that have engaged Arab intellectuals” (p. 9) who “exhibit a profound desire to grapple with the problem of modernity” (p. 2). Boullata uses two essential terms in his study- modernity and modernization - without exploring their epistemological structure and meaning, historical formation (especially in the context of Europe), and social viability in the modern Arab world. He takes it for granted that the Arab world has been a part of the modernization process for many decades. Furthermore, he seems to make a distinction between two types of Arab intellectuals: progressive/modernizing (forces of modernity), and conservative/traditionalist (forces of tradition). He claims that the first type “voiced and articulated the frustration of the Arab masses against Arab regimes and the prevalent culture of Arab society. Their writings were characterized by deep social insight, self-analysis and a great measure of self-criticism” (p. 2). And, “the more progressive among Arab intellectuals have tried to analyze the relationship of contemporary Arabs and the West” (p. 8). Also, “the forces of modernity, using mostly external ideas and models for change, are oriented towards the future, which they see as opening new horizons for the Arabs. Opposing them the forces of tradition, using mostly internal ideas and models for change, are oriented towards the past, which they see as an ideal to be repted because they perceive it as having the promise of certainty and surety of proven success” (p. 6). Finally, “The difference between the extremist Arab thinker on the Right and the extremist Arab thinker on the Left is that the former conforms to a past-oriented ideology which he believes originates in God and divine ...